1997
DOI: 10.1046/j.1460-9592.1997.d01-53.x
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous breathing with the use of a laryngeal mask airway in children: comparison of sevoflurane and isoflurane

Abstract: We compared respiratory parameters during anaesthesia with sevoflurane and isoflurane through a laryngeal mask airway (LMA). Children were anaesthetized with O2 and air with 2.3% (1MAC) sevoflurane (n = 20) or 1.5% (1MAC) isoflurane (n = 20). After insertion of LMA, patients were allowed to breathe spontaneously and respiratory rate (RR) and PECO2 were measured (presurgery state). After the measurement, anaesthetic concentration was increased to 1.3 MAC (3.0% sevoflurane or 2.0% isoflurane) and surgical stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…[33,[42][43][44][45]49] The decreases were smaller than with desflurane, [51] similar to those with isoflurane [45] and generally similar to [49] or significantly lower [44] than with halothane. Changes in blood pressure and the incidence of hypotension (≥30% decrease in systolic blood pressure) were inversely related to age (the study included neonates aged ≤30 days and children aged 0.5 to 12 years).…”
Section: Other Effects (Contd)mentioning
confidence: 71%
See 2 more Smart Citations
“…[33,[42][43][44][45]49] The decreases were smaller than with desflurane, [51] similar to those with isoflurane [45] and generally similar to [49] or significantly lower [44] than with halothane. Changes in blood pressure and the incidence of hypotension (≥30% decrease in systolic blood pressure) were inversely related to age (the study included neonates aged ≤30 days and children aged 0.5 to 12 years).…”
Section: Other Effects (Contd)mentioning
confidence: 71%
“…[33,[41][42][43][44][45][46][47][48] In 2 studies [41,43] these increases were significantly (p < 0.05) greater than those seen with halothane, but in another [44] the difference was not significant. Results of a study conducted in 30 infants (mean age about 6 months) indicate that sevoflurane (1 to 1.5 MAC), unlike halothane, had no significant effect on heart rate versus awake measurements; halothane-induced decreases in this parameter were significant versus sevoflurane values.…”
Section: Other Effects (Contd)mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that LMA insertion time is quicker with sevoflurane than halothane (8). and that cardiorespiratory parameters are similar to isoflurane (9). To our knowledge, there have been no studies comparing the clinical efficacy of sevoflurane and propofol in children.…”
Section: Introductionmentioning
confidence: 99%
“…However, the changes did not show significance after post hoc correction, indicating that changes in RR and MV during muscle traction did not differ between the LR and MR surgeries. In this study, sevoflurane was used for anesthetic maintenance [10,[20][21][22][23]; its effect on respiration has not yet been fully elucidated. We note that the increase in RR (by ~20%) was greater than the magnitude of change in TV (~10%) during muscle traction.…”
Section: Discussionmentioning
confidence: 99%